Factors Influencing Female Workers’ Perception of Sufficient Work Time: A Survey-Based Study - Rahmawati, Nur Anisah; Kurniawati, Eighty Mardiyan (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Women's participation in the labor market has increased significantly, yet challenges related to fair wages, long working hours, and work-life balance persist. This study addresses the factors influencing female workers’ perceptions of sufficient work time among female workers.Methods: This study used secondary data from the 2024 National Labor Force Survey conducted by Indonesia’s Central Bureau of Statistics, focusing on six industrial cities in East Java. A purposive sample of employed women aged 15 years and older with complete data on key variables was selected for the analysis. Data collection was conducted using Computer-Assisted Personal Interviewing (CAPI) through the FASIH application. Statistical analyses were performed with a significance level set at p < 0.05 and 95% confidence intervals (CI).Results: In total, 1,378 female workers completed the survey. Almost all the female workers (94.0%) felt that their working hours were sufficient. Education (p=0.014), length of work (p=0.07), payroll period (0.002), wages according to the district minimum wage (0.000), and long working hours (0.022) were related to perceived work time sufficiency in female workers, while age (p=0.624), marriage (p=0.642), vision impairment (p=0.956), and hearing loss were not related to perceived work time sufficiency.Conclusion: Employment conditions, education levels, and wage systems influenced how women perceive their work time adequacy. Adequate wages, access to education for women, and working hours within healthy limits can improve the work-life balance for women.